Exploring firm-specific deterrents of innovation in micro and small enterprises in Ethiopia - Samuel Godadaw Ayinaddis (Journal of Innovation and Entrepreneurship, 2022)
The paper aims to analyze firm-specific deterrents of innovation in Bahirdar city MSEs in Ethiopia. In order to attain the objective of the study, both descriptive and explanatory research method is used. In this paper, the data were drawn from 310 MSEs firms which were selected by using a simple random sampling technique. The data were analyzed using descriptive and inferential statistics which include mean, standard deviation, and binary logistic regression model. From the model summary, independent variables that were incorporated under the current study, contributed 69.6% of the deterrents of innovation in MSEs as represented by the Nagelkerke R-square. This means that those variables explain about 69.6% of the deterrents of innovation of MSEs, whereas other factors not covered in this study contributed 30.4% to the deterrents of innovation. The results have revealed that research and development are the most critical deterrent factor affecting technological innovation of MSEs at a 1% level of significance. Besides, cost of innovation and firm size factors are the next important deterrent factors affecting technological innovation of the enterprises, followed by human resource factors. Contrarily, variables such as organizational culture and perceived risk factors have not been statistically significant and less likely to affect innovation of MSEs in the current study. The government and other stakeholders need to work hard to encourage innovation among MSEs by providing support, including an increased supply of credit, training, technology support, and provision of micro and small enterprise information services.
Keywords: 650; Deterrents of innovation; Entrepreneurship; Innovation; Micro and small enterprises